Propuesta metodológica para un índice compuesto transversal no compensatorio con variables predeterminadas - Treviño-Cantú, Jesús A. (El Colegio de México, 2023)
This study calculates and measures the stability of four composite indices widely used in the socioeconomic literature: Principal Component Analysis (PCA), Pena's Distance (DP2), the Mazziotta Pareto Index (MPI), and the Geometric Mean (GM). The research proposes a balanced standardization procedure (zEB)that rescales variables to have the same maximum and minimum values between variables, and therefore the same interval, maintaining asymmetry at within an acceptable statistical level. The case study of social backwardness in the states of Mexico in 2020 shows that the GM is the most stable aggregation index either with weighted or unweighted zEB. either with weighted or unweighted data. In addition, the GM is a conceptually coherent index because it is formative and not compensatory, as befits the nature of the phenomenon studied.